Cardenolide biosynthesis in light- and dark-grown Digitalis lanata shoot cultures - Eisenbeiß, Marina; Kreis, Wolfgang; Reinhard, Ernst (Plant Physiology and Biochemistry, 1999)
Shoot cultures of the cardenolide-producing species Digitalis lanata Ehrh. accumulated up to 0.6 μmol cardenolides per g dry mass when cultivated under continuous white light. After transfer to permanent dark, the cardenolide content of cultured shoots gradually decreased and reached non-detectable levels after 12 weeks. After transfer back to light conditions, cardenolides started to accumulate and reached the levels of light-grown controls after 4 weeks. Radiolabelled pregnenolone and progesterone were incorporated into cardenolides in both green light-grown and white dark-grown shoots. It was thus established that cardenolides are synthesised de novo in chloroplast-free tissues without apparent cardenolide accumulation, indicating that these compounds are efficiently turned over in the dark and that tissue differentiation, but not intact chloroplasts, is essential for cardenolide formation. The time course of two late anabolic enzymes of cardenolide metabolism, acetyl-CoA:digitoxin 15'-O-acetyltransferase (DAT, EC 2.3.1.-) and UDP-glucose:digitoxin 16'-glucosyltransferase (DGT, EC 2.4.1.-) was established during transfer of shoots from light to dark and vice versa. Only DAT was affected and was not measurable any more under dark conditions. The DGT may not be down-regulated because of its important, maybe even vital, role as an enzyme providing the vacuolar storage forms of cardenolides. Two catabolic cardenolide-specific enzymes, lanatoside 15'-O-acetylesterase (LAE, EC 3.1.1.6.) and cardenolide 16'-O-glucohydrolase I (CGH I, EC 3.2.1.21), were also investigated and it was demonstrated that CGH I is inactive in dark-grown shoots. These observations indicate that CGH I is not involved in cardenolide degradation in situ, but may instead play a role in cardenolide remetabolisation and activation after wounding or in developmental programs.
UnivIS-Import:2015-03-05:Pub.1999.nat.dbio.LPB.carden_99
Keywords: Biosynthesis; Cardiac glycosides; Digitalis lanata; Enzymes; Pregnenolone; Progesterone; Shoot cultures